Топос Аркадії в повоєнній польській літературі "малої вітчизни" - Довжок, Т. (Київський національний університет імені Тараса Шевченка, 2010)
Досліджено особливості ідилічного часопростору, прообразом якого в повоєнній "кресовій" прозі (А. Кусьнєвіч, З. Гаупт та ін.) є регіон багатокультурного пограниччя Галичини, Поділля, Волині. Описано техніки втілення топосу Аркадії ("зняття шарів палімпсесту", "дозрівання о дитинства", "викриття ілюзії" тощо).

The article examines the features of idyllic chronotop in the post-war boarder land prose (A. Kuśniewicz, Z. Haupt and others) and describes the ways to realization of topos Arcadia ("removing layers of palimpsest", "childhood to maturity", "exposing illusion" etc.). This chronotop is typical of a multicultural frontier region of Galicia, Podolia, Volhynia.
The topos of Arcadia in the post-war Polish literature of "Small Homeland"